Assessment of genetic diversity in fenugreek (Trigonella foenum-graecum) genotypes using morphological and molecular markers - MALOO, S R; SHARMA, RADHESHYAM; JAIN, DEVENDRA; CHAUDHARY, SHARDA; SOAN, HIMANSU (The Indian Journal of Agricultural Sciences, 2020)
Fenugreek (Trigonella foenum-graecum) is one of the most important seed spices possessing aromatic and medicinal properties. Commonly conventional methods based over phenotypic variability are being used by breeders for identification of superior germplasm which are laborious and time consuming. A study was carried out at Department of Molecular Biology and Biotechnology, Rajasthan College of Agriculture, Maharana Pratap University Agriculture and Technology, Udaipur, during 2014–16 to assess the genetic diversity among 20 diverse fenugreek genotypes using morphological and molecular markers for the identification of superior entries. Mean squares due to genotypes were highly significant and wide mean range performance was observed for plant height, pods per plant, test weight, biological yield per plot and harvest index. RAPD analysis was carried out with 25 primers and 21 primers produced 76 bands, in which 37 were polymorphic bands. Average polymorphism was 48.60% and Jaccard’s Similarity Coefficient lies between 0.71 to 0.99. From the results based over morphological and molecular studies it could be concluded that 20 fenugreek entries were classified in 2 clusters through morphological characterization while the same entries were more precisely classified in 5 clusters through RAPD analysis. Superior fenugreek entries were identified for seed yield and its components. Based on the results promising and diverse fenugreek entries will be useful for further breeding programmes.